185 Four-year follow-up study of health hazards among workers handling engineered nanomaterials. (11th October 2013) - Liou, S; Liao, H; Chung, Y; Lai, C; Wang, S; Chiang, H; Li, L; Tsou, T; Lin, M; Lin, C; Li, W; Lee, H
Abstract : Objectives: The aim of this study was to investigate the health hazards in workers exposed to nanoparticles during manufacturing and application of nanomaterials. Methods: For this 4-year longitudinal study, we recruited 283 nanomaterial-handling workers and 213 non-exposed control workers from 15 manufacturing plants in Taiwan. Follow-up measurements were done at 6, 12, 24, 36, and 48 months. Among them, 206 nanomaterial-handling workers and 140 unexposed workers were followed up for more than twice. For each participant, a self-administered questionnaire was distributed to collect work history and personal habits after informed consent. Since there was a lack of equipment for personal sampling and summary index for mixed exposure, we adopted the control banding nanotool risk level matrix to categorise the risk level for each participant. Blood, urine and exhaled breath condensate (EBC) were collected to examine markers of cardiopulmonary injuries, lung and systemic inflammation, oxidative stress, and genotoxicity. Generalised Estimating Equation (GEE) model was applied to analyse these repeated measurements. Results: There were 108 workers in risk level 1, and 91 workers in risk level 2, and 7 in risk level 3. Although depression of antioxidant enzymes and increase of cardiovascular markers were found in the cross-sectional and early follow-up study, no significant difference was revealed between exposed workers and controls in the changes of biomarkers in this 4-year longitudinal study. The non-significant markers included lung injuries markers, cardiovascular disease markers, heart rate variability (HRV), inflammation markers, oxidative stress and lipid peroxidation markers, comet assay, pulmonary function test, and neurobehavioral function test. Conclusions: This longitudinal study suggests that there was no evidence of health hazards among nanomaterials handling workers. The preliminary survey of nanoparticle exposure level in the workplace was quite low. Such exposure level was not high enough to induce systemic health effects in nanoworkers.